Baseado em estórias reais . Based on a True Story - Moraes, Gustavo (Brazil, 2002)
The film was shown at the 2005 Princeton Festival of New Latin American Short Film. In 1972, during Brazil's dictatorship, a young man is arrested while attempting a bank robbery. A journalist who witnesses the event writes an article for her newspaper. In a parallel story, a woman bakes a cake from a recipe.